2011
DOI: 10.1016/j.phrs.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and inter-conversion of sulforaphane and erucin in human subjects consuming broccoli sprouts or broccoli supplement in a cross-over study design

Abstract: Broccoli consumption may reduce the risk of various cancers and many broccoli supplements are now available. The bioavailability and excretion of the mercapturic acid pathway metabolites isothiocyanates after human consumption of broccoli supplements has not been tested. Two important isothiocyanates from broccoli are sulforaphane and erucin. We employed a cross-over study design in which 12 subjects consumed 40 grams of fresh broccoli sprouts followed by a 1 month washout period and then the same 12 subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
165
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(179 citation statements)
references
References 27 publications
8
165
1
1
Order By: Relevance
“…It is relevant to point out that erucin is extensively metabolised to form sulforaphane as a result of the oxidation of its sulphide group and, furthermore, sulforaphane is reduced to form erucin in vivo. Such an inter-conversion of sulforaphane and erucin may occur in vitro during tissue incubation, and in humans consuming broccoli sprouts or broccoli supplements (Kassahun et al, 1997;Clarke et al, 2011). There have been a few studies concerned with the concentrations of isothiocyanates in plasma and/ or their pharmacokinetic behaviour so as to allow the in vitro effects of these compounds to be extrapolated in in vivo situation.…”
Section: Modulation Of Carcinogen-metabolising Enzyme Systems By Isotmentioning
confidence: 99%
See 1 more Smart Citation
“…It is relevant to point out that erucin is extensively metabolised to form sulforaphane as a result of the oxidation of its sulphide group and, furthermore, sulforaphane is reduced to form erucin in vivo. Such an inter-conversion of sulforaphane and erucin may occur in vitro during tissue incubation, and in humans consuming broccoli sprouts or broccoli supplements (Kassahun et al, 1997;Clarke et al, 2011). There have been a few studies concerned with the concentrations of isothiocyanates in plasma and/ or their pharmacokinetic behaviour so as to allow the in vitro effects of these compounds to be extrapolated in in vivo situation.…”
Section: Modulation Of Carcinogen-metabolising Enzyme Systems By Isotmentioning
confidence: 99%
“…In a human study (Cramer et al, 2012), participants consumed meals supplemented with broccoli sprouts equivalent to 70 µmol sulforaphane or glucoraphanin powder equivalent to 120 µmol sulforaphane, achieved plasma levels of about 0.22 µM and 0.25 µM, respectively 3 hours after consumption. In another study, subjects consumed 40 g of broccoli sprouts (150 and 71 µmol glucoraphanin and glucoerucin, respectively) or 6 supplement pills (121 and 40 µmol glucoraphanin and glucoerucin, respectively) achieved maximum plasma concentrations of sulforaphane and erucin metabolites at 3 h post consumption (Clarke et al, 2011). Nevertheless, intracellular concentrations of isothiocyanates may be higher than those in the plasma; it has already been demonstrated that intracellular concentration may reach 200-fold higher than extracellular concentration within a 3 h of exposure (Ye and Zhang, 2001;Zhang and Callaway, 2002).…”
Section: Modulation Of Carcinogen-metabolising Enzyme Systems By Isotmentioning
confidence: 99%
“…397,398 A close investigation of many of the phytochemical-derived supplements popular with consumers reveals that many of these exhibit poor bioavailability, in contrast to that of SFN. 399,400,41 As a result, it is doubtful that some of the bioactive compounds which demonstrate impressive effects in highlypublicised in vitro studies exist in sufficient systemic concentration to exhibit a clinical effect.…”
Section: Sulforaphane's Diverse Modes Of Chemoprotectionmentioning
confidence: 99%
“…A number of MYR-inactive broccoli seed extracts are commercially-available; these products are a source of glucoraphanin but are devoid of the MYR necessary to convert it to SFN on ingestion. 397 …”
Section: Presence Of Erucic Acid In Broccoli Seed Lipid Fractionsmentioning
confidence: 99%
See 1 more Smart Citation